Incorporating collateral information using an adaptive management framework for the regulation of transgenic crops - Linacre, Nicholas A.; Burgman, Mark A.; Ades, Peter K.; Stewart-Oaten, Allen (International Food Policy Research Institute, 2005)
A lack of data often makes biological management decisions difficult and has been an area of contention in the debate over the approval of transgenic crops. Our knowledge of agricultural and natural systems is limited and our ability to gain additional information, quickly and effectively, is often handicapped by statistical complexity. To adequately cope with this requires new approaches and models that integrate decision-making and management. This paper describes one possible approach to the integration of decision-making and management, which may have application for the regulatory approval of transgenic crops. In many situations countries wishing to approve transgenic crops will have limited data on the environmental performance of the crop. The approach outlined in this paper looks at how related information, possibly collected from other countries, might be used to help inform decisions about the approval of transgenic crops. This is done within an integrated decision-making and management framework.-- Authors' Abstract